A efetividade dos instrumentos de financiamento público da FINEP no desenvolvimento do APL eletroeletrônico de Santa Rita do Sapucaí - Rodrigues, Gilka Soares de Moura (2010)
The main objective of the study was to understand effectiveness instruments of public financiai subsidies at APL Eletroeletrônico of Santa Rita do Sapucaí, MG by Financier of Studies and Projects (Financiadora de Estudos e Projetos - FINEP) focusing the engine company of APL, Linear - Equipamentos Eletrônicos S/A. In This study, the principal models on regional development: Local Productive Arrangements (APLs) and Growth Poles were emphasized, because both of them characterized the studied region. The Technological Innovation Law (Lei da Inovação Tecnológica - LlT), which is the main supporter of APLs in Brazil, also was described, as well as financiai agents, the current mechanisms and financing instruments of FINEP and how they are available. Based on the established public policies, by the Federal Government and by the Ministry of Science and Technology (Ministério da Ciência e Tecnologia - MCT) to which FINEP is linked. The study analysed, the context of the APL Eletroeletrônico of Santa Rita do Sapucaí in the case of Linear company through the public financing instruments established for the development of above-mentioned APL. As conclusion to the raised initial question on research it can be understood if there was effectiveness with the public instruments of financing of FINEP on development of APL Eletroeletrônico of Santa Rita do Sapucaí.